ASSESSMENT OF EFFICIENCY OF USING MEDICATIONS IN CHILDREN ON THE MODEL OF ANTIPYRETICS IN AN OUTPATIENT ADMINISTRATION SETTING - L.S. Grishina; M.M. Sadykov; L.Е. Ziganshina (Педиатрическая фармакология, 2009)
The article assesses the efficiency of using medications in children in a outpatient administration setting on the model of antipyretics as medications of first choice in treatment of acute respiratory virus infections over 2004–2008. It looks at the awareness of the patients’ legal representatives in issues of using anti febriles. It shows the efficacy of incorporating a clinical pharmacology unit into the outpatient pediatric practice.Key words: antipyretics, efficiency, children, legal representatives of patients, clinical pharmacology, outpatient administration, children’s clinic.